Factors associated with noncompliance of COVID-19 guidelines recommended by Government of Pakistan for international travelers arriving at Islamabad International Airport - Sara Saeed; Ambreen Chaudhry; Zeeshan Baig; Khurram Akram; Zakir Hussain; Mumtaz Ali Khan; Muhammad Wasif Malik; Aamer Ikram (University of New South Wales, 2022)
'Introduction;: Since the start of pandemic new variants have been evolving and moving from one country to another either by air travel or ground crossings. 'Objective': To find out factors associated with noncompliance of recommended guidelines by international passengers so that we can improve the arrangements at airports where required, improve future preparedness, and give recommendations to concerned authorities for improvement in enforcing guidelines. 'Methodology': A cross-sectional study was carried out at Islamabad International Airport during the months of June and July 2021. The study population included international arriving passengers aged 12 years and above. Questions were asked about following guidelines before boarding, on board, and after disembarkation. Twenty questions were asked to assess compliance level. A median cut off value was set for assessment of noncompliance. 'Results:' The male to female ratio was 1:1. The age range was 12 - 75 years. The odds of noncompliance to guidelines was higher in females compared to males. The results revealed a significant association between region of arrival of respondents and noncompliance. Passengers arriving from Afghanistan, France , UK and USA were more likely to be noncompliant to guidelines (p-value = 0.00). There was a significant association between occupation of participants and noncompliance. Housewives and retired were more likely to be noncompliant (p-value = 0.00). A significant association was observed between vaccinated people and noncompliance. 'Conclusion:' Travelers arriving from some specific countries were noncompliant to guidelines. Vaccinated were most noncompliant which indicates still we need to work on awareness and need legislations, fines or travel restrictions to noncompliant travellers.